Os efeitos da restrição crônica de sono sobre o desempenho de ratos na tarefa de esquiva inibitória - Carvalho, Adriana Neves da Silva [UNIFESP] (2009)
There are numerous studies suggesting that sleep deprivation induce deleterious effects in the rat performance on memory tasks. However, there are but a few studies on the effects of experimental chronic sleep restriction on those tasks. Recently, we observed that rats submitted to a protocol of chronic sleep restriction in which the animals were sleep-deprived for 18h/day and allowed to sleep for 6h in the light phase, during 21 consecutive days, showed no deficits on memory. Here, we investigated the possibility that chronic sleep restriction would impair the performance on the inhibitory avoidance task when rats are allowed to sleep in different circadian phases. Rats were deprived of sleep using the platform method and then trained in a step-through inhibitory avoidance task. One hour after training, the animals were given a retention test. Neither 6h of sleep opportunity (light and dark phase) nor 4h sleep opportunity (light phase) induced impairment on inhibitory avoidance. However, we observed a deficit on performance on inhibitory avoidance task after 4h of sleep opportunity in the dark phase, when there is no coincidence between circadian and homeostatic pressure. Also, 3h of sleep, even in the light phase were not enough to prevent the memory impairment. These results suggest that the memory impairment of sleep deprived rats could be a result of disrupted coincidence between circadian and homeostatic drivers to sleep.